Hobbes on Legal Authority and Political Obligation - Venezia, Luciano. author. aut Link
XII, 161 p.
Keywords: Hobbes on Legal Authority and Political Obligation develops a new interpretation of Hobbes's theory of political obligation. According to the account developed in the book, the directives issued by the sovereign as introducing authoritative requirements, so that subjects are morally obligated to obey them.